Answer:
(n + 1)(3n + 7)
Step-by-step explanation:
3n² + 10n + 7
Consider the factors of the product of the n² term and the constant term which sum to give the coefficient of the n- term.
product = 3 × 7 = 21 and sum = + 10
The factors are + 3 and + 7
Use these factors to split the n- term
3n² + 3n + 7n + 7 ( factor the first/second and third/fourth terms )
3n(n + 1) + 7(n + 1) ← factor out (n + 1) from each term
= (n + 1)(3n + 7) ← in factored form
<u>Answer:</u>
-10,1,19
<u>Step-by-step explanation:</u>
<u></u>
x+y+z = 10 (Equation 1)
2y-x= 12 (Equation 2)
x-y+2z = 7 (Equation 3)
(Equation 2): -x = -2y+12
x = 2y-12 (Equation 4)
(Equation 1) - (Equation 3): 2y-z = 3
-z = -2y+3
z = 2y-3 (Equation 5)
Substitute (4) and (5) into (1)
x+y+z = 10
(2y-12)+y+(2y-3) = 10
5y-15 = 10
5y = 5
y=1
Substitute y=1 into (2)
2y-x= 12
2(1)-x= 12
2-x= 12
-x= 12-2
-x= 10
x= -10
Substitute y=1 and x=-10 into (1)
x+y+z = 10
-10+1+z = 10
z-9 = 10
z = 10+9
z = 19
Order: x = -10, y = 1, and z = 19
So, we need to do the distance she travelled (21 miles) divided by the rate at which she travelled (4 hours). Therefore, because 21 divided by 4 is 5.25, she biked at a speed of 5.25 mph (Miles per hour). So, if she bikes 5.25 miles every hour we can divide 42 by 5.25 to get the time it would take her to travel 42 miles. Now, 42 divided by 5.25 equals 8, so that means for Shelly to bike 42 miles at her average speed of 5.25 mph, it would take her 8 hours.
Answer:
y intercept is -1/2
Step-by-step explanation:
Answer:
=−2x−5y
Step-by-step explanation:
Let's simplify step-by-step.
6x−5y−12x+4x
=6x+−5y+−12x+4x
Combine Like Terms:
=6x+−5y+−12x+4x
=(6x+−12x+4x)+(−5y)
=−2x+−5y